2017
DOI: 10.3390/ijerph14111318
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the SRD5A1 and SRD5A2 Genes in Patients with Benign Prostatic Hyperplasia with Regard to Metabolic Parameters and Selected Hormone Levels

Abstract: Introduction: The etiology of benign prostatic hyperplasia (BPH) has not so far been fully explicated. However, it is assumed that changes in the levels of hormones associated with aging can contribute to the development of prostatic hyperplasia. Dihydrotestosterone combines with the androgen receptor (AR) proteins of the prostate gland. Enzyme activity is based on two isoenzymes: type 1 and type 2. 5α-reductase type 1 is encoded by the SRD5A1 gene, and type 2 is encoded by the SRD5A2 gene. The aim of our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
(30 reference statements)
0
12
0
1
Order By: Relevance
“…Finally, regarding benign prostate diseases, a meta-analysis undertaken in 2017 by Zeng et al ( 85 ) found a risk of developing BPH in individuals carrying the A49T variant (OR=2.75; CI=1.32–5.69), but this was not statistically significance (P=0.373). By contrast, the results of studies concerning the V89L variant and its association with the development of BPH and PSA changes have been contradictory ( 86 , 87 ). A previous study reported that the Val/Leu+Leu/Leu genotype (P=0.047; OR=1.62; CI=1.00–2.61) was associated with the development of this benign condition, but not with the development of PCa ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, regarding benign prostate diseases, a meta-analysis undertaken in 2017 by Zeng et al ( 85 ) found a risk of developing BPH in individuals carrying the A49T variant (OR=2.75; CI=1.32–5.69), but this was not statistically significance (P=0.373). By contrast, the results of studies concerning the V89L variant and its association with the development of BPH and PSA changes have been contradictory ( 86 , 87 ). A previous study reported that the Val/Leu+Leu/Leu genotype (P=0.047; OR=1.62; CI=1.00–2.61) was associated with the development of this benign condition, but not with the development of PCa ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…Постоянная стимуляция андрогеновых рецепторов при прогрессии ДГПЖ необходима для роста и функции ткани ПЖ, путем трансактивации домена, который закодирован в первом экзоне гена АР (Xq 11-12) [25][26][27]. При исследовании полиморфизма генов, кодирующих 5α-редуктазу 2 типа (SRD 5A1 и SRD 5 A2), было установлено, что имеется тесная взаимосвязь между выраженностью полиморфизма генов, объемом ДГПЖ, эффективностью проводимой антиандрогенной терапии и концентрацией половых гормонов и их метаболитов [28,29]. Известно, что α 1 -адренорецепторы непосредственно принимают участие в процессе действия внутриклеточных эффекторов, которые влияют на объем и тонус гладкомышечных элементов ПЖ, что объясняет явный результат их активации [30].…”
Section: патогенетические механизмы дгпжunclassified
“…Serenoa repens extracts: In vitro study of the 5α-reductase activity in a co-culture model for Benign Prostatic Hyperplasia action of enzyme 5α-reductase, which leads to an increase of the prostate size and causes various disorders, especially in the lower urinary tract (1,2). The approach for the treatment and therapy of BPH is mainly based on the use of inhibitors of 5α-reductase enzyme, in particular natural inhibitors, such as the active compounds present in the alcoholic extracts deriving from species Serenoa repens, a typical palm common in the Subtropical sandy soils and in the southern coasts of the United States.…”
Section: Original Papermentioning
confidence: 99%
“…Benign Prostatic Hyperplasia (BPH) is a form of benign tumor that occurs in humans mainly with ageing. In fact, it affects more than 50% of over 50 years old males, with an incidence rate directly proportional to age (1). It is characterized by an increased synthesis of dihydrotestosterone (DHT) starting from testosterone, due to the several EU Member States (including Italy) and belonging to the class of drugs employed to counter the increase in prostatic volume in males with BPH, have been tested.…”
Section: Introductionmentioning
confidence: 99%